Joint Configuration of Composite Beams to Reinforced Concrete Wall. (2016) - Pop, Maria; Kiss, Zoltan; Pernes, Paul
Abstract: Multi Storied structures are used worldwide and have outstanding advantages in the use of composite materials in structural application. This study heads to an experimental and to a numerical study to reproduce the behavior on a composite joint configuration. The experimental and numerical calibration and validation of the behavior is treated, for the simulation of the composite beam to reinforced concrete wall configuration subjected to a monotonic loading, to determine deformation capacity of the joint.